Лебедушка: [стихи] / Сергей Есенин - Есенин Сергей Александрович (Библиотека младшего школьника)
Экземпляры: ф.8 (20131128) / Инвентарный номер: 55506 / Цена: / Сис.шифр: 84(2Рос=Рус)6-5 / Авт.знак: Е 82 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-5